Studying on regeneration of several cassava varieties (Manihot esculenta Crantz) via friable embryogenic callus - Minh Hong, Nguyen Thi; Hoai Thuong, Nguyen Thi; Ngoc, Pham Bich; Ha, Chu Hoang (Vietnam Journal of Biotechnology, 2018)
Cassava (Manihotesculenta Crantz) is considered as one of the most important food crops which has high economic value in many areas. It is very neccessay to perfect the cassava regeneration protocol for genetic transformation purpose. In this study, cassava regeneration via friable embryogenic callus (FEC) from tip bud, young stem, pieces of leaf had been optimized in five cassava varieties which were planted in Vietnam including KM 140 (S1), NgheAn white cassava (S2), Lang Son red cassava (S3), HoaBinh high – yield cassava (S4) and Huay Bong (S5). The results indicated that on MS medium supplemented with 10 mg/l Picloram, the proportion of callus formation was very high, reached from 90 to 100%. In the case of using tip buds, after three weeks, calli were transferred to MS medium adding 5 mg/l picloram and 0,2 mg/l IBA. The proportion of FEC formation reached 41,1 – 80,4 % after 8 weeks of cultivation in all studied Cassava varieties. The samples were transferred to MS medium adding 0,3 mg/l BAP to elongate shoots in 4 weeks. The highest regeneration rate belonged to S1, and was 61,67%. Three weeks after shoot transferring on MS medium, the complete seedlings were grown in substrate which was composed by TN01 and husk hun with ratio of 6:4 in greenhouse. As a result, the rate of survival plants reached to 95%. The process of regeneration of cassava through embryonic calli could be applied for the improvement of desired cassava varieties by method of genetic engineering.